Role of Age and Sex on the Incidence of Leukemia in a Sample of Iraqi Patients - Dahlia N. AL-Saidi (Medical Journal of Babylon)
Background: Leukemia accounts for 8% of the total cancers in the population and is known as the world’s fifth most common type. Leukemia is not just a pediatric disease as most people assume. The disease consists of four main types and several sub-types, and only some are more common among children. Leukemic cells affect the other types of blood cells produced by the bone marrow, including red blood cells and platelets. Leukemia is typically caused by certain genetic defects that cannot be changed. Objectives: To find if there is a correlation between sex and age with the incidence of leukemia. However, the majority of epidemiologic studies have shown links between leukemia incidence and potential risk factors, including ionizing radiation exposure and chemicals. They have also shown that some of these factors, like smoking, infections, and family history of cancer, are simply modifiable. Understanding pertinent risk factors may therefore be important for leukemia prevention and mitigation. Materials and Methods: The current study was conducted on 100 patients with leukemia of all kinds, who visited Baghdad Teaching Hospital in the Medical City complex in Bagdad, Iraq, from January to September 2022. The diagnosis was confirmed based on bone marrow aspiration, blood film, flow cytometry analysis of cells, and genetic analysis using PCR. Results: In the current study, the results showed that acute lymphocytic leukemia has the high-test prevalence (42%) among cases followed by acute myelogenous leukemia (30%), chronic lymphocytic leukemia (9%), chronic myelogenous leukemia (7%), hairy cell leukemia (5%), natural killer cell leukemia (4%), and mast cell leukemia (3%). There was a significant association between sex and leukemia incidence (P = 0.009). Also, there was a significant correlation between age and the incidence of leukemia (P = 0.013). Conclusion: There is a correlation between sex and age with the incidence of leukemia.